The Increasing Occurrence of Infectious Diseases in Childhood: Is It Linked with Declining Vaccination Rates Across Society? - Sztybór, Izabela; Kułak, Klaudia Brygida; Palacz, Karolina Alicja; Pliszka, Marzena; Janik, Izabela; Gadżała, Katarzyna; Chamera-Cyrek, Katarzyna; Koman, Anna Maria; Kuśmierska, Martyna; Przygodzka, Sabina (Journal of Education, Health and Sport, 2024)
Introduction. Childhood infectious diseases have been a significant medical problem, with a global increase in recent years. Modern diagnostic methods and new vaccinations are available. Poland is part of the WHO-coordinated global measles and rubella elimination program. Controversy surrounds mandatory and recommended vaccinations in Poland. There has been a concerning increase in the abandonment of vaccinating children, leading to a resurgence of infectious diseases. In 2024, the WHO reported a significant increase in measles cases in the European region, including in Poland. It's crucial to remind people of these diseases and warn them about the complications they bring. Aim of study. The aim of this study is to investigate the increasing occurrence of infectious diseases in childhood and examine the correlation with declining vaccination rates across society. Materials and methods. An unsystematic review of scientific literature was conducted, employing specific keywords such as „measles,” „pertussis,” „rubella,” „infectious diseases,” „vaccination,” and „hib.” The review was executed on the PubMed database, analyzing a total of 59 sources published until the conclusion of 2024. Conclusions. To control and eliminate infectious diseases, it is vital to maintain and improve vaccination rates. Policymakers and healthcare providers should prioritize immunization programs and address barriers to vaccine access. Further research is crucial to develop comprehensive strategies for increasing vaccination coverage and understanding vaccine-preventable diseases in modern public health challenges.